Risk revisited - Caplan, Patricia (Pluto Press, 2000)
Annotation Looking at the concept of risk from a cross-cultural perspective, the contributors challenge the Eurocentric frameworks within which notions of risk are more commonly considered. They argue that perceptions of danger, and sources of anxiety, are far more socially and culturally constructed - and far more contingent - than risk theorists generally admit. Topics covered include prostitutes in London; AIDS in Tanzania; the cease-fire in Northern Ireland; the volcanic eruptions in Montserrat; modernisation in Amazonia; and the BSE scare in Britain.
Keywords: Risk -- Sociological aspects.; Risk perception.; Risk perception -- Cross-cultural studies.; Risque -- Aspect sociologique.; Perception du risque.; Perception du risque -- Études transculturelles.; PSYCHOLOGY -- Social Psychology.; POLITICAL SCIENCE -- Political Ideologies -- Democracy.; Risk perception; Risk -- Sociological aspects; Risico nemen.; Interculturele vergelijking.; Sociologische aspecten.; Cross-cultural studies